Analysis of intact phosphoinositides in biological samples - Pettitt, Trevor R; Dove, Stephen K; Lubben, Anneke; Calaminus, Simon D J; Wakelam, Michael J O (Journal of lipid research, 2006)
It is now apparent that each of the known, naturally occurring polyphosphoinositides, the phosphatidylinositol monophosphates (PtdIns3P, PtdIns4P, PtdIns5P), phosphatidylinositol bisphosphates [PtdIns(3,4)P(2), PtdIns(3,5)P(2), PtdIns(4,5)P(2)], and phosphatidylinositol trisphosphate [PtdIns(3,4,5)P(3)], have distinct roles in regulating many cellular events, including intracellular signaling, migration, and vesicular trafficking. Traditional identification techniques require [(32)P]inorganic phosphate or [(3)H]inositol radiolabeling, acidified lipid extraction, deacylation, and ion-exchange head group separation, which are time-consuming and not suitable for samples in which radiolabeling is impractical, thus greatly restricting the study of these lipids in many physiologically relevant systems. Thus, we have developed a novel, high-efficiency, buffered citrate extraction methodology to minimize acid-induced phosphoinositide degradation, together with a high-sensitivity liquid chromatography-mass spectrometry (LC-MS) protocol using an acetonitrile-chloroform-methanol-water-ethylamine gradient with a microbore silica column that enables the identification and quantification of all phosphoinositides in a sample. The liquid chromatograph is sufficient to resolve PtdInsP(3) and PtdInsP(2) regioisomers; however, the PtdInsP regioisomers require a combination of LC and diagnostic fragmentation to MS(3). Data are presented using this approach for the analysis of phosphoinositides in human platelet and yeast samples.